Efeito da espessura e da cor de uma cerâmica de dissilicato de lítio na resistência de união de cimentos resinosos à dentina - Ricardo Antonio Alpino Rodrigues (2017)
The dual resin cements have been largely used to fix indirect restorations due to their enhanced mechanical and aesthetic properties. The light transmission through the restorative materials decreases, thereby compromising the mechanical properties of luting agent. The objective of the present study was to evaluate the effect of different shades and thicknesses of a lithium dissilicate glass ceramic (IPS e.max CAD) on bond strength of resin cements to dentin. One hundred and ten (110) flat dentin surfaces from sound extracted human molars were polished and standardized using 320-grit SiC and randomly divided into two resin cement groups (RelyX U200, 3M/ESPE or RelyX Ultimate, 3M/ESPE); Each cement group was divided into subgroups: control, color (2 levels: A2 and A3) and thickness of lithium dissilicate ceramic of energy (2 levels: 2 mm and 3 mm (n = 11). (Bluephase, Ivoclar Vivadent, 800 mW / cm2, for 20 s) for the production of resin cements, a ceramic for interposition between the resin cement and light source in the experiments groups. The teeth were stored in distilled water at 37 ° C for 24 h. Shear bond strength test was performed on a shear bond testing device (Bisco Shear Bond tester, Schaumburg, IL, USA). The load was applied at 0.5 mm/min to the resin cement and dentin interface until failure. The failure mode was analyzed under stereoscopic with 40x magnification. Scanning electron microscope images were obtained from representative fractured surfaces. For each resin cement data was analyzed by Kruskal-Wallis (p<0,05) with Post-hoc Dunn-Bonferroni correction. The results showed that for cement RelyX U200 resin cement, the shade and thickness did not affected the bond strength to dentin when compared to the control group (p=0.103). For RelyX Ultimate, there was a significant difference between control and A2/3mm (p=0.001); between control and A3/2 mm (p=0.003); and between control and A3-3 mm (p=0.001) groups. It can be concluded that the lithium dissilicate glass ceramic had no effect on the bond strength of RelyX U200 to dentin. The bonding of RelyX Ultimate to dentin depended on shade or thickness of the glass ceramic. In general, shear bond strength value of RelyX Ultimate was higher than RelyX U200.